A new species of rock skink (Scincidae: Liopholis) from the Central Ranges bioregion of arid Australia - Farquhar, Jules E.; Mulder, Jordan A.; Russell, Wyn; Haines, Margaret L.; Rangers, Anangu; Chapple, David G. (Zootaxa, 2024)
A new species of rock skink Liopholis Fitzinger 1843 (Scincidae) is described from the Mann-Musgrave Ranges of north-western South Australia. Liopholis margaretae sensu lato (Storr 1968) is currently known to occur in two disjunct populations: the MacDonnell Ranges bioregion and nearby regions in the Northern Territory, and the Central Ranges bioregion in South Australia. Based on morphological examination of both museum and field specimens, as well as on newly generated molecular data, we show that specimens from these two ranges constitute distinct species. The new species, Liopholis aputja sp. nov. is endemic to a specific geological landform (Mann-Musgrave Ranges) within the Central Ranges bioregion, and is estimated to have diverged from the MacDonnell Ranges population during widespread aridification of the Miocene. Liopholis aputja sp. nov. is distinguished from congeners by a combination of its moderately large size (SVL up to 135 mm), relatively pointed snout, smooth dorsal scales, black and calloused subdigital lamellae and soles of feet, and possessing usually six supraciliary scales and usually four enlarged ear lobules. This new species adds to the list of endemic herpetofauna recognised in the Central Ranges bioregion.